2015
DOI: 10.1016/j.bbamem.2014.10.040
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial voltage-dependent anion channel 1 in tumor cells

Abstract: VDAC1 is found at the crossroads of metabolic and survival pathways. VDAC1 controls metabolic cross-talk between mitochondria and the rest of the cell by allowing the influx and efflux of metabolites, ions, nucleotides, Ca2+ and more. The location of VDAC1 at the outer mitochondrial membrane also enables its interaction with proteins that mediate and regulate the integration of mitochondrial functions with cellular activities. As a transporter of metabolites, VDAC1 contributes to the metabolic phenotype of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
254
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(273 citation statements)
references
References 417 publications
(819 reference statements)
9
254
0
6
Order By: Relevance
“…HK bound to VDAC1 offers the enzyme direct access to mitochondrial sources of ATP and greater affinity for Mg 2ϩ -ATP (16). This is lost upon HK detachment from VDAC1 as induced by A␤.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HK bound to VDAC1 offers the enzyme direct access to mitochondrial sources of ATP and greater affinity for Mg 2ϩ -ATP (16). This is lost upon HK detachment from VDAC1 as induced by A␤.…”
Section: Discussionmentioning
confidence: 99%
“…VDAC1 transports ions, Ca 2ϩ , cholesterol, and metabolites across the outer mitochondrial membrane and participates in the release of mitochondrial pro-apoptotic proteins to the cytosol and interacts with apoptosis regulatory proteins (15,16). Thus VDAC1 appears to be a convergence point for a variety of cell survival and death signals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Other reports also indicate PPID overexpression in many tumor types. 38 In addition to aberrations of these genes in lymphoma, our results showed that expression of SLC25A31 could be regulated by VPA treatment.…”
mentioning
confidence: 99%
“…VDAC1, as a gatekeeper in the outer mitochondrial membrane, has the pivotal functions in cancer cells through the management of anti/pro-apoptotic proteins during intrinsic apoptosis (Shoshan-Barmatz et al 2015). Current evidence has demonstrated the participating of VDAC1 in drug resistance, carcinogenesis, cell metabolism and apoptosis (Shoshan-Barmatz et al 2015;Wang et al 2016). Low expression VDAC1 induces a non-apoptotic role and high expression VDAC1 occurs following apoptosis induction by chemotherapeutic agents .…”
Section: Discussionmentioning
confidence: 99%